2009
DOI: 10.1136/thx.2008.101758
|View full text |Cite
|
Sign up to set email alerts
|

Association of prematurity, lung disease and body size with lung volume and ventilation inhomogeneity in unsedated neonates: a multicentre study

Abstract: Background: Previous studies have suggested that preterm birth with or without subsequent chronic lung disease is associated with reduced functional residual capacity (FRC) and increased ventilation inhomogeneity in the neonatal period. We aimed to establish whether such findings are associated with the degree of prematurity, neonatal respiratory illness and disproportionate somatic growth. Methods: Multiple breath washout measurements using an ultrasonic flowmeter were obtained from 219 infants on 306 test oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
83
4
5

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 53 publications
(48 reference statements)
19
83
4
5
Order By: Relevance
“…We found no significant difference between the CLDI and control groups for the nondimensional slopes over the region that alveolar gas concentration was estimated. This finding suggests marked ventilation inhomogeneity was not present in our CLDI group, which is consistent with data presented by Hü lskamp and colleagues, who reported a small effect on lung clearance index (LCI) with neonatal oxygen exposure; 100 days of oxygen exposure during the neonatal period correlated with an increase in LCI from approximately 7.0 to 7.3 (18). This small increase in LCI in infants with CLDI contrasts to a much higher LCI observed in clinically stable outpatient infants with cystic fibrosis (CF), who have an LCI of 8.4 (19).…”
Section: Discussionsupporting
confidence: 81%
“…We found no significant difference between the CLDI and control groups for the nondimensional slopes over the region that alveolar gas concentration was estimated. This finding suggests marked ventilation inhomogeneity was not present in our CLDI group, which is consistent with data presented by Hü lskamp and colleagues, who reported a small effect on lung clearance index (LCI) with neonatal oxygen exposure; 100 days of oxygen exposure during the neonatal period correlated with an increase in LCI from approximately 7.0 to 7.3 (18). This small increase in LCI in infants with CLDI contrasts to a much higher LCI observed in clinically stable outpatient infants with cystic fibrosis (CF), who have an LCI of 8.4 (19).…”
Section: Discussionsupporting
confidence: 81%
“…Some studies showed decreased endexpiratory volume [functional residual capacity (FRC)] and lung clearance index (LCI) (2) in sedated infants, whereas other studies in infants during natural sleep could not confirm these observed differences in FRC and LCI between healthy infants and infants with CLD (3). We (4) and other authors (3) indicated that the latter findings are in line with the following clinical observations: infants with CLD in natural sleep may have a high capacity to maintain relatively normal lung volume and relatively normal gas exchange, despite alterations to their lung mechanics, whereas this capacity may be reduced during sedation.…”
supporting
confidence: 75%
“…*: p,0.05; **: p,0.01; ***: p,0.0001. in persons with cystic fibrosis [30] it has not been found to be particularly discriminative when assessing BPD or prematurity either during infancy [31,35] or in the current study.…”
Section: Nature Of Underlying Pathophysiologymentioning
confidence: 62%